Traumatic Cochlear Implant Electrode Extrusion: Considerations, Management, and Outcome. (31st July 2021) - Chan, Ching Yee; Wang, Feifan; Omar, Haryani; Tan, Henry Kun Kiaang
Abstract : Cochlear implantation is the mainstay for patients with severe to profound hearing loss that do not benefit from hearing aids. Falls and head trauma can cause direct damage to the implant, of which hard failure is the most common complication. Traumatic electrode migration is an uncommon occurrence. Our patient underwent successful electrode advancement of a partially migrated, normal functioning electrode two months after head injury. We discuss the factors influencing the decision-making process, progress, and outcomes.